Differences in Mechanisms of Orographic Rainfall over West Sumatra (Case Study: 10 April and 23 April 2004) - Wendi Harjupa; Toyoshi Shimomai; Hiroyuki Hashiguchi; Yasushi Fujiyoshi; Masayuki Kawashima (JIF (Jurnal Ilmu Fisika))
Two different mechanisms of orographic rainfall enhancementÂ Â in West Sumatra were investigated utilizing observed data during the Coupling Processes in the Equatorial Atmosphere (CPEA)-I campaign. The variation of the atmospheric conditions during the campaign was shown by rainfall, surface wind, humidity, and stability index. An X-band Doppler radar captured the atmospheric conditions related to the enhancement of orographic rainfall mechanisms. The dry and less stable atmospheric conditions resulted in the convective type of rainfall. In contrast, the humid and stable atmospheric conditions brought the large-scale rainfall in the mountainous region where the events took place coincided with the inactive and active MJO phases. .